2020
DOI: 10.3390/e22040415
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Multifractal and Organization/Order Structure in Suomi-NPP VIIRS Normalized Difference Vegetation Index Series of Wildfire Affected and Unaffected Sites by Using the Multifractal Detrended Fluctuation Analysis and the Fisher–Shannon Analysis

Abstract: The analysis of vegetation dynamics affected by wildfires contributes to the understanding of ecological changes under disturbances. The use of the Normalized Difference Vegetation Index (NDVI) of satellite time series can effectively contribute to this investigation. In this paper, we employed the methods of multifractal detrended fluctuation analysis (MFDFA) and Fisher-Shannon (FS) analysis to investigate the NDVI series acquired from the Visible Infrared Imaging Radiometer Suite (VIIRS) of the Suomi Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The scaling property of these NDVI original series agrees with earlier works in which the persistence condition for crops is also reported through H(q = 2) or Hurst index using R/S method [21,26]. However, the results have shown that this series could have a multifractal nature as investigated by Li et al [28] and Ba et al [29] over the vegetation dynamic of areas affected by the fire through multifractal analysis achieving the same conclusion. Several parameters can be calculated, as the ones showed in Table 7, given more possibilities to classify the NDVI series studied.…”
Section: Scaling Characteristics Of Ndvi Original Seriessupporting
confidence: 88%
See 1 more Smart Citation
“…The scaling property of these NDVI original series agrees with earlier works in which the persistence condition for crops is also reported through H(q = 2) or Hurst index using R/S method [21,26]. However, the results have shown that this series could have a multifractal nature as investigated by Li et al [28] and Ba et al [29] over the vegetation dynamic of areas affected by the fire through multifractal analysis achieving the same conclusion. Several parameters can be calculated, as the ones showed in Table 7, given more possibilities to classify the NDVI series studied.…”
Section: Scaling Characteristics Of Ndvi Original Seriessupporting
confidence: 88%
“…GSF focuses on the absolute values of the differences that occur at different time scales, and it represents an excellent tool to study the dynamic of a series from a multiscaling point of view, as explained in the materials and methods section of this study. Recently, several works have approached the study of NDVI series using multiscaling analysis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of Fisher Information (FI) was introduced in the statistical theory estimation (Fisher, 1925), while the special case of FI of a location parameter of a parametric distribution was termed FIM (Frieden, 1990). Subsequently, FIM has been used to describe physical systems (Frieden, 1990;Boumali and Labidi, 2018), and has been applied for time series analysis in physiology (Martin et al, 1999), geophysics (Telesca et al, 2011;Balasis et al, 2016), ecology (Ba et al, 2020), meteorology (Pierini et al, 2016;Guignard et al, 2019b), hydrology (Pierini et al, 2011(Pierini et al, , 2015Lovallo et al, 2013), and social behaviour (Li et al, 2020). For continuous one dimensional variable X with probability density function (pdf) f(x) the FIM I X is defined as (Vignat and Bercher, 2003)…”
Section: The Fisher-shannon Methodsmentioning
confidence: 99%
“…The GSF has been used to study vegetation [ 34 ] and other geophysical data [ 35 ]. More recently, MF-DFA has been used to study the long-term ecosystem dynamics at a large scale [ 36 , 37 , 38 , 39 ] and compare the dynamics of areas affected and unaffected by fire [ 40 ]. MF-DFA allows the study of multiscaling on vegetation and the detection of whether it is related to long-term correlations or broad probability density functions.…”
Section: Introductionmentioning
confidence: 99%